Southeast Asia transformed a geography of change - Chia, Lin Sien (Institute of Southeast Asian Studies, 2003)
Bringing together the combined insights by specialists who have worked and lived in the region, the theme of this book is change and transformation. The authors identify the trends and forces that propel the region along, and then bring in discussions on key issues.